2020
DOI: 10.1002/app.50412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between pea and soy protein‐based bioplastics obtained by injection molding

Abstract: The elaboration of bioplastics from renewable polymers (e.g., proteins) is a field with great potential for industrial applications such as food packaging and agriculture. This study evaluates the development of bioplastic systems by injection molding using two different raw materials: soy protein isolate (SPI) and pea protein isolate (PPI). Both proteins are by‐products, which lowers the price of processed bioplastics. However, it is necessary to control their properties during the manufacture processing, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Finally, the degradation time of each bioplastic matrix is indicated in Table 1. As can be seen, higher mould temperatures lead to more durable bioplastics, probably due to the better mechanical properties observed with increasing temperature, as is reported in previous works [51]. However, the incorporation of nanoparticles in the bioplastics caused this degradation to be faster, except for the systems with 1.0 wt% nanoparticles.…”
Section: Biodegradabilitysupporting
confidence: 74%
“…Finally, the degradation time of each bioplastic matrix is indicated in Table 1. As can be seen, higher mould temperatures lead to more durable bioplastics, probably due to the better mechanical properties observed with increasing temperature, as is reported in previous works [51]. However, the incorporation of nanoparticles in the bioplastics caused this degradation to be faster, except for the systems with 1.0 wt% nanoparticles.…”
Section: Biodegradabilitysupporting
confidence: 74%
“…), processing parameters (flow rate, voltage, distance between the needle and the collector, etc. ), and environmental parameters, such as temperature and relative humidity [1][2][3][4]. In addition, electrospinning is a versatile process that allows obtaining structured nanofibers, which are formed by micro-and nanosized fibers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the soluble matter loss remained constant at 48%, which means that, apart from glycerol, because of the high solubility of pea protein, a small amount of soluble protein was also lost during immersion [44]. These results have been corroborated by Jia et al [39], who showed that the addition of cinnamaldehyde as crosslinking agent produced a decrease in the water absorption [40].…”
Section: Functional Propertiesmentioning
confidence: 73%